Korean as a Foreign Language Learners’ Motivation: Language Learning Stories from Indonesian Learners - Chandra, Yuliyanto (Universitas Islam Negeri Walisongo Semarang, 2024)
Although the Korean Wave has grown exponentially in Indonesia, much of the linguistic landscape has not received enough attention in the literature, especially the motivational aspect. Based on the L2 Motivation Self System (L2MSS), the present study focuses on the language learning stories of Indonesian learners of Korean as a foreign language (KFL)—consisting of two females and one male. Their language learning stories cover the past, present, and future trajectories of their language learning. Four salient themes are generated through the interview–the questions of which were partially based on the Language Learning Story Interview. The first theme is related to the pure interest in the popular culture of Korea—mostly related to the exponential growth of the Korean Wave. The second theme is characterized by the aspiration to get jobs in Korea. The third theme concerns education or the desire to pursue higher education in Korea. Lastly, parental support and intercultural marriage form the last source of motivation and contribute to creating a supporting learning environment. Conclusively, this study reveals that Indonesian KFL learners mostly exhibit both ideal L2 self and ought-to L2 self–with the former being more dominant than the latter. Implications of the study are also provided.